SMARANDACHE ANTI ZERO DIVISORS - Hassan, Rebin M.; Awla, Suham H. (Science Journal of University of Zakho, 2025)
In this paper, we study and discuss the concept of Smarandache anti zero divisor (SAZD) element of the ring and the group ring , where is a cyclic group of order generated by . Moreover, we introduce and discuss the concept of SAZD ideal of the ring . Some results related to the given concepts are proved in detail. Accordingly, a Computer Algebra System (GAP) is used to verify the results of this study